2004
DOI: 10.1042/bst0320614
|View full text |Cite
|
Sign up to set email alerts
|

Choice of a start codon in a single transcript determines DNA ligase 1 isoform production and intracellular targeting in Arabidopsis thaliana

Abstract: DNA ligase 1 (AtLIG1) is the only essential DNA ligase activity in Arabidopsis and is implicated in the important processes of DNA replication, repair and recombination and in transgene insertion during Agrobacterium-mediated plant transformations. The mitochondrial and nuclear forms of DNA ligase 1 in Arabidopsis are translated from a single mRNA species through the control of translation initiation from either the first (M1) or second (M2) in-frame AUG codons respectively. Translation from a third in-frame A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…In case of the DNA ligase 1, translation initiation from a first in-frame start codon produces a protein that is exclusively targeted to mitochondria, while the use of an alternative second start codon produces a protein that is found only in the nucleus (Sunderland et al 2006). The existence of a chloroplast-localized protein initiated at a potential third AUG that was previously proposed (Sunderland et al 2004) could not be confirmed.…”
Section: Introductionmentioning
confidence: 91%
“…In case of the DNA ligase 1, translation initiation from a first in-frame start codon produces a protein that is exclusively targeted to mitochondria, while the use of an alternative second start codon produces a protein that is found only in the nucleus (Sunderland et al 2006). The existence of a chloroplast-localized protein initiated at a potential third AUG that was previously proposed (Sunderland et al 2004) could not be confirmed.…”
Section: Introductionmentioning
confidence: 91%
“…The nucleotide context around the alternative start codons in the AtLIG1 transcripts affects the translation initiation to ensure a balanced synthesis of both nuclear and mitochondrial AtLIG1 isoforms, probably via a context-dependent leaky scanning. (24) Alternative TISs and leaky scanning are responsible for the synthesis of plastidic and cytoplasmic/ nuclear isoforms of tRNA ligase of Arabidopsis thaliana and Oryza sativa, plastidic and mitochondrial isoforms of spinach protoporphyrinogen oxidase and arabidopsis DNA polymerase. (15,25,26) The mRNA of a human spastin gene contains two alternative translation start sites and produces two protein isoforms, 68 and 60 kDa, respectively.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…What became evident with the complete sequencing of both the mitochondrial and nuclear genomes was the added complexity and mixed evolutionary origin of the components involved in expressing the mitochondrial genome. The basic replication machinery involves at least a DNA polymerase (Christensen et al, 2005), a DNA gyrase (Wall et al, 2004) and a DNA ligase (Sunderland et al, 2004(Sunderland et al, , 2006. Plant mitochondrial genomes are organised as multiple circular molecules that undergo a high frequency of inter-and intramolecular recombination (Lonsdale et al, 1984;Mackenzie and McIntosh, 1999).…”
Section: Mitochondrial Genome Structure and Replicationmentioning
confidence: 98%